Strategi Bauran Komunikasi Pemasaran Program Sosial Sahabat Relawan Komunitas Sekolah Marjinal Yogyakarta - Yudaninggar, Kartika Sari; Eszi, Jasmine Aunillah; Estiningsih, Estiningsih (Jurnal Pewarta Indonesia, 2024)
The Marginal School Community has one program, namely Volunteer Friends. This program is a one-day volunteer program teaching marginalized children. This research discusses and describes the marketing communication strategies used by Marginal School Communities. This research uses the theory of segmentation, targeting, positioning, marketing communication, and descriptive methods. The data collection techniques used were interviews, observation, and documentation. The triangulation used by researchers is source triangulation. The results of this research show that to promote the Sahabat Relawan program, the Marginal School Community applies segmentation, targeting, and positioning and a marketing communication mix of sales promotion, events, and experience, public relations and publicity, online and social media marketing, mobile marketing, and personal selling.